Knowledge, Attitude, and Practice toward COVID-19 among Healthy Population in the Philippines - Tuppal, Cyruz P.; Ninobla, Marina Magnolia G.; Ruiz, Mara Gerbabe D.; Loresco, Richard D.; Tuppal, Shanine Mae P.; Panes, Iril I.; Oducado, Ryan Michael F.; Prudencio, Denise Angelo M.; Vega, Paolo D.; Eribal, Mark John E.; Real, Don Vicente P.; Roa, Mary Nellie T. (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: COVID-19 pandemic has become a severe health threat to the Philippines and around the world. At the early onset of the pandemic, it is imperative to measure the knowledge, attitude, and practice (KAP) among healthy individuals to better understand the causes, transmission, and preventive measures. Purpose: This study aimed to identify the knowledge, attitude, and practice towards COVID-19 in a healthy Filipino population during the early onset of the pandemic outbreak.Methods: This cross-sectional rapid online and web-based survey was conducted among healthy Filipino population. A total of 1634 subjects participated via the Google survey link. Descriptive statistics were used to describe the respondents' profile characteristics and KAP scores. The One-Way ANOVA or independent sample t-test was used to measure KAP scores' differences when grouped according to respondents' profile characteristics. Pearson correlation was used to measure the relationship among the KAP scores. The data were all analyzed using the SPSS version 26.0. Results: The overall knowledge scores revealed 67.7%. Filipinos believed COVID-19 would finally be successfully controlled and confident that the Philippines can win the battle against the virus through preventive practices. KAP scores showed significant differences with age, sex (p<0.000), and place of residence (p<0.000), occupation (p<0.000), and marital status (p<0.000). A significant positive low correlation between knowledge and practice (r=0.076, p<0.01), attitude and practice (r=0.100, p<0.01).Conclusion: Albeit a low knowledge of COVID-19, healthy Filipino populations had a positive attitude and compliant with the preventive measures. This study hopes to contribute to the growing corpus of literature on COVID-19 to provide evidence-based information towards health promotion, illness prevention, and control of possible virus' spread.